Test negative case–control study of COVID-19 vaccine effectiveness for symptomatic SARS-CoV-2 infection among healthcare workers: Zambia, 2021–2022 - Francis Dien Mwansa; Nathan Kapata; Roma Chilengi; Sombo Fwoloshi; Muzala Kapina; Kunda Musonda; Nyambe Sinyange; Patricia Bobo; Leora R Feldstein; Oliver Mweso; John Simwanza; Warren Malambo; et al. (BMJ Open)
Objectives The study aim was to evaluate vaccine effectiveness (VE) of COVID-19 vaccines in preventing symptomatic COVID-19 among healthcare workers (HCWs) in Zambia. We sought to answer the question, ‘What is the vaccine effectiveness of a complete schedule of the SARS-CoV-2 vaccine in preventing symptomatic COVID-19 among HCWs in Zambia?’Design/setting We conducted a test-negative case–control study among HCWs across different levels of health facilities in Zambia offering point of care testing for COVID-19 from May 2021 to March 2022.Participants 1767 participants entered the study and completed it. Cases were HCWs with laboratory-confirmed SARS-CoV-2 and controls were HCWs who tested SARS-CoV-2 negative. Consented HCWs with documented history of vaccination for COVID-19 (vaccinated HCWs only) were included in the study. HCWs with unknown test results and unknown vaccination status, were excluded.Primary and secondary outcome measures The primary outcome was VE among symptomatic HCWs. Secondary outcomes were VE by: SARS-CoV-2 variant strains based on the predominant variant circulating in Zambia (Delta during May 2021 to November 2021 and Omicron during December 2021 to March 2022), duration since vaccination and vaccine product.Results We recruited 1145 symptomatic HCWs. The median age was 30 years (IQR: 26–38) and 789 (68.9%) were women. Two hundred and eighty-two (24.6%) were fully vaccinated. The median time to full vaccination was 102 days (IQR: 56–144). VE against symptomatic SARS-CoV-2 infection was 72.7% (95% CI: 61.9% to 80.7%) for fully vaccinated participants. VE was 79.4% (95% CI: 58.2% to 90.7%) during the Delta period and 37.5% (95% CI: −7.0% to 63.3%) during the Omicron period.Conclusions COVID-19 vaccines were effective in reducing symptomatic SARS-CoV-2 among Zambian HCWs when the Delta variant was circulating but not when Omicron was circulating. This could be related to immune evasive characteristics and/or waning immunity. These findings support accelerating COVID-19 booster dosing with bivalent vaccines as part of the vaccination programme to reduce COVID-19 in Zambia.